The Electron Density: A Fidelity Witness for Quantum Computation - Skogh, Mårten; Rahm, Martin; Lolur, Phalgun; Barucha-Dobrautz, Werner (Chalmers University of Technology, 2024)
Electron densities calculated using physical (superconducting qubits) and simulated quantum computers for the hydrogen molecule (H2), lithium hydride (LiH), di-lithium (Li2), and hydrogen cyanide (HCN). Additionally, the reduced one-particle density matrix (1-RDM) and results of topological analysis for the mentioned molecules. Calculations on physical quantum hardware were performed on Särimner, a quantum processor with three superconducting qubits. Simulations of quantum computers were performed with Qiskit.

Elektrontäthet beräknad med hjälp av fysiska (supraledande kvantbitar) och simulerade kvantdatorer för väte molekylen (H2), litiumhydrid (LiH), di-litium (Li2) samt vätecyanid (HCN). Inkluderar även den reducerad enpartikeltäthetsmatrisen (one-particle reduced density matrix, 1-RDM) och resultat av topologisk analys av elektrontätheterna för molekylerna. Beräkningar på fysisk hårdvara utfördes på Särimner, en kvantprocessor med tre supraledande kvantbitar. Simulering av kvantdatorer utfördes med Qiskit,
The Electron Density: A Fidelity Witness for Quantum Computation
Keywords: computational chemistry; beräkningskemi; quantum computers; kvantdatorer; electronic structure; Other Physics Topics; Annan fysik; Theoretical Chemistry; Teoretisk kemi